Physical and biological characterizations of TiNbSn/(Mg) system produced by powder metallurgy for use as prostheses material - Rossi, Mariana Correa [UNESP]; Bayerlein, Daniel Leal; Brandão, Jaqueline de Souza [UNESP]; Pfeifer, João Pedro Hübbe [UNESP]; Rosa, Gustavo dos Santos [UNESP]; Silva, William de Melo [UNESP]; Martinez, Luis Gallego; Saeki, Margarida Juri [UNESP]; Alves, Ana Liz Garcia [UNESP] (Elsevier, 2021)
Titanium scaffolds with non-toxic β stabilizing elements (Nb and Sn), Ti–34Nb–6Sn (TNS), and with magnesium as spacer (TNS/M), were processed by powder metallurgy, and sintered at 800 °C. The X-ray diffraction (XRD) pattern showed that materials are biphasic alloys, presenting 45 to 42% (wt %) in hcp (α-phase) and the rest is bcc (β-phase), and the presence of a slight peak relating to TiO2 in both materials. Pores of approximately 50 μm for TNS and 300 μm to TNS/M were observed in the micrographic analysis by scanning electron microscopy (SEM). The wettability was higher for TNS/M compared to TNS. The elastic modulus was higher for TNS compared to TNS/M. Stem cells derived from equine bone marrow (BMMSCs) were used for in vitro assays. The morphologic and adhesion evaluation after 72 h, carried out by direct contact assay with the materials showed that the BMMSCs were anchored and adhered to the porous scaffolds, in the way the cytoplasmic extension was observed. The cellular migration, using the “wound healing” method, was significant for the groups treated with conditioned medium with materials in 24 h. Osteogenic differentiation of BMMSCs, assessed by calcium deposition and staining with Alizarin Red, was greater in the conditioned medium with TNS/M in 10 days of culture. Since the biological effects was good and the elastic modulus decreased in the system with magnesium is a promising new content titanium alloy for biomedical application.
Keywords: Magnesium; Powder metallurgy; Scaffold; Titanium-niobium-tin